2023
DOI: 10.3390/nano13172483
|View full text |Cite
|
Sign up to set email alerts
|

Characterising Hydroxyapatite Deposited from Solution onto Novel Substrates: Growth Mechanism and Physical Properties

Bríd Murphy,
Jhonattan Baez,
Mick A. Morris

Abstract: Whilst titanium, stainless steel, and cobalt-chrome alloys are the most common materials for use in orthopaedic implant devices, there are significant advantages in moving to alternative non-metallic substrates. Substrates such as polymers may have advantageous mechanical biological properties whilst other substrates may bring unique capability. A key challenge in the use of non-metal products is producing substrates which can be modified to allow the formation of well-adhered hydroxyapatite films which promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…These peaks indicate calcium's binding to phosphate groups, which is in line with the literature. This confirms the presence of hydroxyapatite in the scaffold, as calcium is found in a chemical environment common to calcium phosphates [45,46].…”
Section: Xpssupporting
confidence: 73%
“…These peaks indicate calcium's binding to phosphate groups, which is in line with the literature. This confirms the presence of hydroxyapatite in the scaffold, as calcium is found in a chemical environment common to calcium phosphates [45,46].…”
Section: Xpssupporting
confidence: 73%
“…The HAp-FCOL/CS membrane exhibited significantly higher Ca and P signals, along with increased CPS and smoother spectral lines (Figure A,B), suggesting enhanced mineral growth. The binding energy data revealed that the HAp-FCOL/CS membrane showed a P 2p 3/2 peak at 132.6 eV, indicative of HAp phosphates . The Ca 2p 3/2 peak at the lower binding energies of 347.0 and 350.4 eV, indicated the deposition of calcium phosphate (Figure A).…”
Section: Resultsmentioning
confidence: 98%
“…The Ca 2p and P 2p core scan of FCOL/CS membrane showed Ca and P detection at a low level (Figure D,E), consistent with EDS mapping results (Figure S2). The low concentration of Ca can be attributed to contamination or limited uptake from the colloidal solution …”
Section: Resultsmentioning
confidence: 99%
“…Solution-based HA processes highlight a requirement to regulate the ionic strength of solutions [16][17][18][19]. Chemical precipitation is advantageous in forming HA nanoparticles and nano-powders because the phases of HA can be controlled during this process, but it has not yet been extensively explored as a coating technique [20][21][22][23][24][25]. Similarly, precipitation of Ca 2+ and PO 4 3− ions out of a solution onto a surface to form a HA layer has been achieved with relevant precursors under specific conditions of pH and temperature on collagen or bone interfaces [26,27].…”
Section: Introductionmentioning
confidence: 99%